El sistema jurídico: del plano a la realidad - Ovejero Silva, Bruno (2020)
The paper is a preliminary study of a general theory of law and its main object is to describe the key characteristics of the legal system. The aim is to define the concepts that allow the design of a kind of "blueprint" from which the reader can understand what a legal system is, what its components are and how it works on specific legal conflicts. Thus, concepts and terminologies that are often confusingly used among lawyers and judges will be refined (norm, rule, standard, validity, efficiency, application, interpretation, subsumption, balancing). The paper highlights the importance of certain theoretical and methodological decisions in practical legal reasoning, the usefulness of clear terminologies, the identification of the place that moral evaluation occupies in that reasoning, the importance of the construction of solid premises, the problems generated by extreme simplifications (formalism and skepticism) and the need to recognize a halo of uncertainty in any normative solution that, however, does not mean disregarding any objective meaning of the norm.